Population‐based assessment of kaposi sarcoma‐associated herpesvirus DNA in plasma among Ugandans. Issue 9 (12th July 2013) - Shebl, Fatma M.; Emmanuel, Benjamin; Bunts, Lisa; Biryahwaho, Benon; Kiruthu, Christine; Huang, Meei‐Li; Pfeiffer, Ruth M.; Casper, Corey; Mbulaiteye, Sam M.
Abstract Risk of Kaposi sarcoma (KS) is linked to detection of Kaposi sarcoma‐associated herpesvirus (KSHV) DNA in plasma, but little is known about the prevalence and risk factors for plasma KSHV DNA detection among the general population where KS is endemic. Correlates of KSHV plasma detection were investigated in a population‐based sample of adult Ugandans (15–59 years) who participated in an HIV/AIDS serobehavioral survey in 2004/2005. KSHV DNA was measured in plasma of 1, 080 KSHV seropositive and 356 KSHV seronegative persons using polymerase chain reaction (PCR). KSHV DNA in plasma was detected in 157 (8.7%) persons; of these 149 (95%) were KSHV seropositive and 8 (5%) were seronegative. Detection of KSHV DNA in plasma was significantly associated with male sex (P < 0.001), older age (P = 0.003), residence in a rural versus urban area (P = 0.002), geographic region (P = 0.02), and being KSHV seropositive (13.8% seropositive vs. 2.3% seronegative, P < 0.001). In a multivariable model, KSHV DNA plasma quantity was significantly higher in men (P = 0.002), inversely associated with age (P = 0.05), and residing in an urban area (P = 0.01). In Uganda, KSHV is detected more frequently in the plasma of adult males and residents of rural regions, potentially explaining the increased risk of KS in these subsets of the Ugandan population. J. Med. Virol. 85:1602–1610, 2013. © 2013 Wiley Periodicals, Inc.